EPIDEMIOLOGICAL ASPECTS OF HEAD LICE IN CHILDREN ATTENDED TO AT A PUBLIC HOSPITAL IN UBERLÂNDIA, MINAS GERAIS STATE, BRAZIL - Messias Marinho, Mariana; Araújo Milan, Beatriz; Borges-Moroni, Raquel; Mendes, Julio; Tonissi Moroni, Fábio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Pediculosis capitis is a public health problem not only in Brazil, but also in many countries worldwide. Children are the most likely population group to be infested. The purpose of this study was to verify the prevalence of head lice in children seen at the public hospital in Uberlândia, Minas Gerais State, and factors associated with ectoparasitosis in this group. In addition, data about the transmission, prevention and control were obtained from the children’s parents or guardians. The scalp and hair of every child aged 2 to 12, attended to at the hospital pediatric outpatient clinic from 2015 to 2017, were examined. Questionnaires and characterization sheets were also used to obtain and record the information. The overall prevalence rate observed was 2.8%. The highest prevalence rates were observed in girls with medium length hair. Children presented a relatively low prevalence of head lice in the parasitological examinations. However, the answers to the questionnaires indicated that this ectoparasitosis is common in this population group. All the children examined were of school age, and their parents or guardians indicated the school environment as the main source of infestations. The responses to the questionnaires also highlighted evidence of negligence on the part of guardians of positive children regarding the occurrence of this ectoparasitosis. The information obtained indicates that authorities should design/improve their plans of action regarding guidelines for parents or guardians for adequate prevention and control of this ectoparasitosis.